Understanding The Financial Performance Dynamics And Its Implications On Firm Value A Qualitative Study On ROA, Financial Distress, And Debt To Equity Ratio - Gibrananda Putra Kanaan; Bethanya Sanggarwati; Aretha Widi Ailani (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This study aims to investigate the relationship between financial performance indicators (ROA, Financial Distress, and Debt to Equity Ratio) and firm value. Employing a purposive sampling technique, data were gathered from a diverse range of companies across industries. The study utilized thematic analysis to interpret the qualitative data. Results suggest nuanced dynamics between financial performance metrics and firm value, revealing the multifaceted nature of their interplay. While ROA reflects short-term profitability, Financial Distress highlights operational challenges, and Debt to Equity Ratio underscores financial leverage. The findings underscore the importance of considering various financial performance indicators holistically to comprehend their impact on firm value comprehensively. This research contributes to a deeper understanding of the complex relationship between financial performance dynamics and firm valuation in the business landscape.